Complete Convergence for Weighted Sums of Sequences of Negatively Dependent Random Variables - Qunying Wu (Journal of Probability and Statistics)
Applying to the moment inequality of negatively dependent random variables the complete convergence for weighted sums of sequences of negatively dependent random variables is discussed. As a result, complete convergence theorems for negatively dependent sequences of random variables are extended.